MAXILLOFACIAL FRACTURES IN PATIENTS WITH MULTIPLE INJURIES AND POLYTRAUMA - Elitsa G.Deliverska (Peytchinski Publishing, 2016)
Introduction Severity and complexity of combined maxillofacial trauma require not only multidisciplinary approach, but prevention of trauma is also of extreme importance, as this may reduce direct and indirect social economic losses. Understanding the trauma etiology, types, and severity may support clinical priorities determination, increase treatment effectiveness, and also may achieve certain trauma prevention. In polytrauma patients, omissions in early injury diagnostics is often observed, especially in uncooperative and intoxicated patients, as well as in patients in unconscious state. MFS is important in multiple trauma patients and is essential for exact and correct diagnosis, as well as for adequate maxillofacial trauma treatment. Purpose The aim of this study is to identify the maxillofacial fractures in patients with multiple trauma or polytrauma and to analyze whether there are any factors related to associated injuries. Material and methods A total of 352 traumatic patients were retrospectively and prospectively examined for the period of 6 years (05.2005 - 12.2011), treated at Department of Oral and Maxillofacial surgery at the St. Anna University Hospital , Sofia, on grounds of the accurately kept hospital documents in conformity with accepted standards and with ethical requirements for performing such studies. Results Associated injuries were observed in 129 patients (36%). In combined maxillofacial trauma (СMFT), the most common maxillofacial fracture is lower jaw fracture (46.5%), followed by zygomatic bone trauma (34.9%) and nasal bones trauma (21.7%). The occurrence of associated injury correlated significantly with trauma mechanism and fracture type; high-speed accidents and severe facial fractures were significant predictors of associated injury. Alcohol plays a key role in maxillofacial trauma appearance, whereas the alcohol relation is significant with interpersonal injuries (42%), with falling (20%) and with motor vehicle accidents (5.7%). Conclusion Applying of multidisciplinary approach (anaesthesiologists, neurosurgeons, abdominal surgeons, traumatologists, maxillofacial surgeons) in traumatic patients provides optimum results and the best possible outcome in their treatment.